THE INFLUENCE OF STREET TREES ON URBAN MICROCLIMATE - Martini, Angeline; Biondi, Daniela; Batista, Antonio Carlos (Floresta, 2020)
The microclimatic improvement is often cited as one of the benefits generated by urban trees, however, there are few studies which quantitatively address this effect. The aim of this paper was to compare the microclimate of streets with and without trees. Therefore, three samples containing a stretch of street with and without trees were selected, with the street with trees being composed of different species. The temperature, relative humidity and wind speed data were measured by automatic Kestrel® meteorological ministations installed on the street with trees and another in the street without trees. The data collection period was from 9 AM to 3 PM, and the monitoring interval was every 1 minute during all four seasons starting in the winter of 2011. The comparative analyses were done using the Student’s t-test (99%). The results indicated that the air temperature in a street with trees was on average 1.7 °C lower than a street without trees, the relative humidity was 6.9% higher and the wind speed was 0.04 m/s lower. There was no statistical difference for temperature between the street with “ipê” in the winter and spring. There was no difference for wind speed in the summer between the street with other trees and the street with “ipê” and “tipuana”. It was concluded that street trees provide a pleasant microclimate, and this influence was statistically significant.